(untitled) (Confluenţe Bibliologice, 2025)
Let us pray unceasingly to God and our Mother of God and then we will have necessarily the mercy of God, for persistent prayers are heard in Heaven. Through sincere prayer, from the bottom of the heart spoken, we are asking the GOD to help get rid of sins. The author brings us an Orthodox education in popular style that is based on the teaching of Orthodox Christian faith. The author urges us to welcome with an open heart the Orthodox education of our parents, to be receptive to advice pertaining to faith. So we enjoy the God’s mercy and his blessings.